Study of Pancasila Values in Community Creativity in Marindal Village I "Entrepreneurship Training for Mothers: Acrylic" - Silitonga, Dania Amanda Br; Ramadhani, Nadia; Situngkir, Cindy Via (Holistic Science, 2024)
Pancasila is the foundation of the state for the Indonesian nation. Pancasila as the basis of state guidance has its own philosophy that is deeply rooted in the Indonesian nation. Pancasila has moral elements, a value system, a spirit of development, as well as a system in the Pancasila Economy. The moral philosophy of Pancasila Economics can be interpreted as a unified measure, or a norm that regulates the patterns of thinking and patterns of action of economic actors in the Pancasila Economic system. Pancasila entrepreneurship is expected to be able to encourage all components of society to carry out economic activities so that they can grow an independent people's economy, in accordance with the practice of Pancasila as the nation's guide to life. This research aims to see to what extent an understanding of Pancasila values can influence the entrepreneurial interest of mothers in Marindal I Village. The research method used is a qualitative research method